The comparative review model in measuring Islamic and conventional banking system of the Islamic banking culture in Malaysia - Rosfazila Abd Rahman,; Novel Lyndon,; Khairul Anuar Ahmad Abdul Razif Zaini,; Mohd Shahrul Nizam Mohd Danuri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
There is a narrative inclusion of Islamic values that are driven by religion as a living culture in Malaysia. Islamic banking institutions involved in the implementation of the Islamic Banking System which provides an opportunity for the general public to incorporate Islam into their financial context lives. The Islamic banking institution is responsible for pioneering the Islamic financial services industry. Therefore, the main issue is to what extent Islamic banking culture has been practiced. The main objective is to measure the Islamic and conventional banking system in the context of Islamic banking culture by using a comparative review model. The study was using the qualitative approach that involved structured interviews with the officers of Sharia’, operations, products and services personnel and the top management. The data analysis was carried out by employing the ATLAS.ti software. The finding indicates the principles in the Islamic banking system do not permit any business activities related to interest (riba), gambling (maisir) and speculative elements (gharar). The principles in the conventional banking system are based on the capitalist system through the theory of demand and supply. The meaning and understanding of the Islamic organisation culture shows are very significant differences between Islamic and conventional banking. The concept of Islamic banking is based on social justice while the concept of the conventional banking is focused on maximizing profit. The implication is that there are several aspects such as leadership, product development and innovation as well as services which need to be improved and given ample consideration.